2020
DOI: 10.3390/ijerph17114127
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence, Burnout, and Work Engagement: The Moderating Effect of Coping in the Democratic Republic of Congo

Abstract: Research on coping, sense of coherence, burnout, and work engagement is well documented in western countries. However, a void of studies exists on how coping mechanisms can moderate the relationship among sense of coherence, burnout, and work engagement in a manufacturing company in the Democratic Republic of Congo (DRC). The objective of this research was to examine the moderating effect of coping (COP) in the relationship between sense of coherence (SOC), burnout (BO), and work engagement (WE). The study emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…A study by Mitonga-Monga and Mayer (2020) points out that work engagement of employees is strongly and positively impacted on by a high level of coping, a high sense of coherence level and a low level of burnout in the Democratic Republic of Congo in Central Africa. Employees with a high level or work engagement do positively engage, perform, and are productive.…”
Section: Work Engagementmentioning
confidence: 99%
“…A study by Mitonga-Monga and Mayer (2020) points out that work engagement of employees is strongly and positively impacted on by a high level of coping, a high sense of coherence level and a low level of burnout in the Democratic Republic of Congo in Central Africa. Employees with a high level or work engagement do positively engage, perform, and are productive.…”
Section: Work Engagementmentioning
confidence: 99%
“…The SOC is a source of health promotion and a good predictor of burnout, depression, and job satisfaction rates ( Masanotti et al, 2020 ). Coping has been positively related to the SOC, and both SOC and engagement have been negatively related to exhaustion ( Mitonga-Monga and Mayer, 2020 ). It is known that the sense of coherence has a negative correlation with developing post-traumatic stress, which could be equalled to the stress produced by the COVID-19 pandemic, though this correlation is positive with regards to tolerance to extraversion and frustration ( Frommberger et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is still uncertain evidence on the positive effects of training on such resilience ( Kunzler et al, 2020 ). Coping skills have a moderating effect regarding the SOC and engagement variables ( Mitonga-Monga and Mayer, 2020 ). It has been proven that taking action on the social capital of companies generates well-being among their workers and also benefits the organisation, which gains efficiency and lower turnover rates ( Jutengren et al, 2020 ) and that those who engage deeply in worthwhile activities enjoy better health and well-being, have stronger and more abundant social ties, and even greater resistance to stress, something not so clear when there is a great deal of environmental uncertainty ( Burrow and Hill, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Jeremy Mitonga-Monga and Claude-Hélène Mayer [ 19 ], present empirical research findings on coping, SOC, burnout, and work engagement in the context of the Democratic Republic of Congo (DRC), where a void in research on salutogenesis and coping still exists. The authors examined the moderating effect of coping in the relationships between SOC, burnout, and work engagement and found that there is a positive relationship between coping and SOC; however, SOC is negatively related to work engagement and burnout.…”
Section: The Contributions In This Special Issuementioning
confidence: 99%